Long-term efficacy and safety of endoscopic surgery versus small bone window craniotomy for spontaneous supratentorial intracerebral hemorrhage: a meta-analysis and trial sequential analysis - Chen Guo; Yang Bai; Xiaobin Zhang; Pinjing Zhang; Song Han; Di Fan (BMC Neurology)
Abstract Background and aims Endoscopic surgery (ES) and small bone window craniotomy (SBWC) are commonly used methods for hematoma removal in cases of intracerebral hemorrhage (ICH). However, their long-term efficacy and safety remain uncertain. Methods A systematic search was performed in the PubMed, Embase, and Cochrane Library databases from inception to June 30, 2024. The primary outcomes assessed were the 6-month favorable functional outcome rate and the hematoma evacuation rate. Following the meta-analysis, a trial sequential analysis (TSA) was conducted to validate the findings. Results Six randomized controlled trials were included in the meta-analysis. ES demonstrated a higher 6-month favorable functional outcome rate compared to SBWC (56.8% vs. 48.0%, relative risk [RR] 1.20, 95% confidence interval [CI] 1.05–1.38, I 2 = 28%), with TSA supporting this result. The hematoma evacuation rate was also higher in the ES group (mean difference [MD] 6.41, 95% CI 1.83–10.99, I² = 95%); however, the TSA did not support this result due to the potential false-positive. Additionally, ES was associated with shorter operation times, less blood loss during surgery, and a lower pneumonia rate compared to SBWC (MD -112.35, 95% CI -165.27 to -59.43; MD -151.22, 95% CI -279.60 to -22.84; RR 0.68, 95% CI 0.51–0.91). Conclusions The meta-analysis and TSA indicate that ES offers better long-term efficacy, shorter operation times, less blood loss, and a lower rate of pneumonia compared to SBWC. Therefore, prioritizing ES over SBWC for treating ICH appears to be a reasonable approach.